Through hole bone repair material and preparation method thereof

By using natural loofah templates and multi-component composites, the problem of mismatch between pore penetration and pore size of existing materials is solved, and effective repair and reconstruction of bone tissue is achieved.

CN119746147AActive Publication Date: 2025-04-04ZHONG DING KAI RUI TECH CO LTD

Patent Information

Application Number
CN202411942354.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The pore penetration rate and pore size of existing bone repair materials are difficult to match the structure of bone tissue, resulting in insufficient blood vessel growth, tissue diffusion and cell growth, and limited repair effect.

Method used

Using natural loofah as a template, a composite material with loofah structure is formed by selecting a multi-component composite material and loofah, and the loofah is decomposed by ablation heat to remove the loofah, and finally a bone tissue repair material with completely penetrated pores.

Benefits of technology

Prepare bone repair materials with full pore penetration and adjustable pore size and porosity to provide sufficient channels for blood, blood vessels and tissue fluids, and promote the repair and reconstruction of bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212818020000052
    Figure BDA0005212818020000052
  • Figure BDA0005212818020000053
    Figure BDA0005212818020000053
  • Figure BDA0005212818020000071
    Figure BDA0005212818020000071
Patent Text Reader

Abstract

The invention belongs to the field of bone repair materials, and particularly relates to a bone repair material with a through hole structure and a preparation method of the bone repair material. The invention provides a preparation method of a through hole bone repair material. The preparation method comprises the following steps: 1) preparing bone repair raw material slurry: uniformly mixing raw materials of the bone repair material with water to form the bone repair raw material slurry; 2) preparing a bone repair preform; and 3) sintering treatment. After being pyrolyzed at 550 DEG C, the through composite bone repair / bone reconstruction material with the loofah sponge reversed-phase structure contains magnesium hydrogen phosphate with relatively good solubility and degradability, calcium hydrogen phosphate capable of being slowly degraded, calcium sulfate capable of being quickly degraded and absorbed, osteogenic elements including calcium and phosphorus and a magnesium element capable of promoting bone tissue formation; and the material can be gradually degraded from one side in contact with bone tissue, provides components in the whole process of repairing and reconstructing the bone tissue from a wound surface, and promotes tissue repairing and reconstruction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of bone repair materials, in particular to a bone repair material with a through-hole structure and a preparation method thereof. Background Art

[0002] Bone tissue is the support system of the human body, and is the core system that bears the weight, movement and activity of the human body. Bones are divided into compact bone and cancellous bone. Compact bone is composed of closely arranged bone plates, which are formed by parallel arrangement of bone gelatin fibers buried in a calcified matrix, with uniform thickness. Between the two bone plates, there are a series of neatly arranged cell pits, which have osteocytes with multiple protrusions, connected to each other by capillaries. The bone plates arranged on the surface of the bone are the outer ring bone plates, and the bone plates arranged around the medullary cavity are the inner ring bone plates. There are many concentric circles between the inner and outer ring bone plates, which are called Haversian bone plates. The central tube is the Haversian canal, which is parallel to the long axis of the bone and has branches connected to form a network, and blood vessels and nerves pass through the tube. Cancellous bone is a mesh structure with many large gaps formed by bone plates, and there is bone marrow in the mesh. Cancellous bone exists at the femoral end of long bones, short bones and the inside of irregular bones. Bone tissue is the main component of various bones in the skeletal system. Bones are the support of the body and protect soft organs. Muscles are attached to them and serve as levers for movement organs. The functions of bone tissue in the human body are (1) support and protection of the body; (2) it concentrates 99% of the body's calcium and is an organ that maintains blood calcium balance. Only an appropriate blood calcium concentration can ensure the normal functioning of the heart; (3) hematopoietic function. There are a large number of bone marrow stem cells in the bone marrow, which can be induced to differentiate into various blood cells and enter the blood.

[0003] Therefore, protecting the stability of bone tissue structure is one of the most important factors to ensure human health. However, due to various factors such as disease, dysplasia, traffic accidents and aging, bone tissue necrosis, damage and loss of function are caused, and a large amount of biomaterials are needed as bone tissue repair and replacement. Bone tissue is the basic system that supports and maintains the normal physiological functions of the human body.

[0004] According to the structural and functional requirements of bone tissue, the repair material that matches the bone tissue should have the same or similar structure as the original bone tissue, so that blood vessels can grow into it quickly, tissue fluid can diffuse into it, and bone cells can grow inside the material, gradually completing the repair and reconstruction of bone tissue. Therefore, the bone repair material should have through pores, matching porosity and relatively matching pore size, so as to meet the requirements of blood vessel growth, tissue diffusion and cell growth and proliferation inside the material, penetrate the material and form bone tissue. According to this requirement, porous sponges, physical foaming and chemical foaming agent foaming materials have relatively low pore penetration rates, are difficult to match the structure of bone tissue, and have limited repair effects. Summary of the invention

[0005] Based on the above technical defects, the present invention uses natural loofah as a template, selects a multi-component composite material and loofah to form a composite material with a loofah structure, and then removes the loofah in the composite material through ablation thermal decomposition, and finally forms a bone tissue repair material with completely through pores. The present invention can also control the pore size by controlling the diameter of the loofah fiber through treatment, and control the porosity and density by the amount of loofah grouting and the molding strength of the calcium-phosphorus composite material to prepare a bone repair material with completely through pores and adjustable pore size and porosity, thereby providing sufficient channels for blood, blood vessels and tissue fluid, and promoting the repair and reconstruction of bone tissue.

[0006] The technical solution of the present invention:

[0007] The first technical problem to be solved by the present invention is to provide a method for preparing a through-hole bone repair material, the preparation method comprising the following steps:

[0008] 1) Preparing bone repair raw material slurry: mixing the raw material of the bone repair material with water to form a bone repair raw material slurry;

[0009] 2) preparing a bone repair preform: placing the bone repair raw material slurry in a loofah to fully immerse the loofah so that the bone repair slurry fills the loofah, and then solidifying the slurry to obtain a bone repair preform;

[0010] 3) Sintering treatment: The bone repair preform is sintered to remove the loofah, so as to obtain the bone repair material with a through-hole structure.

[0011] Furthermore, in step 1), the raw materials of the bone repair material include components in the following proportions: 35 to 55 parts by weight of calcium-phosphate-magnesium complex salt, 25 to 55 parts by weight of calcium sulfate hemihydrate, and 0 to 5 parts by weight (preferably 1 to 5 parts by weight) of magnesium pyrophosphate; wherein the molar ratio of magnesium to calcium in the calcium-phosphate-magnesium complex salt is 0.1 to 0.5:1.

[0012] Furthermore, in step 1), the ratio of the raw material of the bone repair material to water is 1:0.5-1.5 (g / mL).

[0013] Further, in step 1), the calcium-phosphorus-magnesium composite salt is prepared by the following method: magnesium salt, calcium salt and phosphorus-containing substance are mixed and ground, then water is added to make a paste, and then vacuum dried to obtain the calcium-phosphorus-magnesium composite salt; wherein the phosphorus-containing substance is calcium dihydrogen phosphate (Ca(H 2 PO 4 ) 2 , adenosine triphosphate (ATP) or cyclic adenosine monophosphate (cAMP).

[0014] Further, the magnesium salt is MgO or MgCO 3 At least one of the calcium salts, wherein the calcium salt is CaO or CaCO 3At least one of .

[0015] Further, in step 1), the bone repair raw material slurry is prepared by the following method:

[0016] (1) Weigh 40-50 g of magnesium oxide, 50-60 g of calcium oxide, and 450-470 g of calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100-150 ml of deionized water, stir for 25-35 minutes, mix well, and dry at 70-80° C. for 5-10 hours to form a calcium-magnesium-phosphorus complex 1;

[0017] Weigh 20-40 g of magnesium oxide, 14-28 g of calcium oxide, and 493-553 g of a phosphorus-containing substance, mix and grind to 200 mesh, add 140-160 ml of deionized water, stir for 25-35 minutes, mix evenly, and dry at 70-80° C. for 5-10 hours to form a calcium-magnesium-phosphorus complex 2;

[0018] Weigh 1 / 150-180 g of the composite and 2 / 30-50 g of the composite and mix them to form component A;

[0019] 2) Weigh 450-550 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 110-130° C. and 0.1-0.5 MPa for 5-10 hours to form calcium sulfate hemihydrate, which is then ground to 200 mesh or more as component B;

[0020] 3) weighing magnesium pyrophosphate and grinding it to 200 mesh or above to form component C;

[0021] 4) Mix 200-210 g of component A, 100-120 g of component B and 5-10 g of component C, add 150-250 ml of deionized water to mix into a slurry to form a bone repair raw material slurry.

[0022] Furthermore, in step 2), the loofah is pretreated before use so that the fiber diameter of the loofah is 200 to 1000 μm.

[0023] Further, in step 2), the pretreatment method is: firstly segment the selected loofah according to its veins, and cut it into regular cubes with a length of 10 mm to 200 mm, a width of 10 mm to 50 mm, and a height of 0.5 mm to 20 mm; then soak it in a treatment solvent, and then dry it for standby use; the treatment solvent is selected from: sodium hydroxide-hydrogen peroxide solution, lithium chloride-dimethylacetamide solution, lithium bromide-dimethylacetamide solution, lithium chloride-dimethylformamide solution, lithium bromide-dimethylformamide solution or cuprammonia solution, and the soaking treatment reduces the fiber diameter of the loofah to obtain a finer and finer loofah.

[0024] Furthermore, the method for preparing a bone repair preform in step 2) is as follows: placing the pretreated loofah in a metal mold, pouring the bone repair raw material slurry obtained in step 1) into the loofah in the mold, using different pressures according to the viscosity of the slurry to control the density and strength of the loofah cuboid after the slurry is poured, and adjusting the solidification time in the mold according to the change in the slurry composition to form a loofah cuboid filled with slurry; after complete solidification, the bone repair preform is obtained, and the mold is opened to take it out for use.

[0025] Further, in step 3), the sintering process is as follows: the bone repair preform is placed in a muffle furnace, gradually heated to 100-120°C and retained for 30-45 minutes, then heated to 200-250°C and retained for 30-60 minutes, and then heated to 500-550°C and retained for 5-12 hours. In this process, the loofah has been decomposed by high temperature and removed from the preform in the form of carbon dioxide and water. The vacancies left after the decomposition of the loofah fibers form fiber channels like the original loofah, forming the final product, a through-hole composite bone repair and reconstruction material with a loofah inverse structure.

[0026] Furthermore, the preparation method of the through-hole bone repair material also includes step 4): post-processing the through-hole bone repair material according to clinical requirements: such as cutting and grinding the shape and size, washing with injection water, drying, using radiation sterilization or epoxy sterilization, and finally packaging for use.

[0027] The second technical problem to be solved by the present invention is to provide a through-hole bone repair material, which is prepared by the above-mentioned preparation method.

[0028] The beneficial effects of the present invention are:

[0029] The through-composite bone repair / bone reconstruction material with a luffa inverse structure provided by the present invention contains magnesium hydrogen phosphate with good solubility and degradability, calcium hydrogen phosphate that can be slowly degraded, and calcium sulfate that can be rapidly degraded and absorbed after being pyrolyzed at 550° C. It has osteogenic elements calcium and phosphorus and magnesium elements that promote the formation of bone tissue, and can gradually degrade from the side in contact with the bone tissue, provide components in the whole process of repairing and reconstructing the bone tissue from the wound surface, and promote tissue repair and reconstruction. In addition, the obtained material has full through-porosity after the luffa fiber is decomposed, which can provide sufficient space for tissue fluid and blood vessels to grow into, can make the formed new bone through, can quickly form continuous through-bone tissue, and accelerate the degradation and absorption of the material. And its degradation rate can be controlled according to the composition to match the regeneration and reconstruction of bone tissue. It can be widely used in the repair and reconstruction of bone trauma and defects. DETAILED DESCRIPTION

[0030] The first step of the present invention is to select loofah as a template. Loofah is formed by interweaving filamentous vascular bundles, mostly in the shape of long prisms or long cylinders, slightly curved, 30 to 70 cm long, and 7 to 10 cm in diameter. The surface is pale yellowish white. It is light, tough, elastic, and cannot be broken. The cross section shows three chambers of the ovary, which are hollow and present a relatively regular three-dimensional structure. The diameter of the loofah fiber bundle is generally, and its diameter can be from the thicker bundle fiber (2000 μm), which is generally tubular, and is not consistent with the pore size required by capillaries and bone cells. The present invention cleans the loofah obtained from the loofah and then dries it naturally. Then, it is divided according to the loofah veins and cut into regular cubes with a length of 10 mm to 200 mm, a width of 10 mm to 50 mm, and a height of 0.5 to 20 mm; then a pretreatment solvent is used to reduce the fiber diameter of the loofah to obtain a finer and finer loofah. Then, it is dried for use. The invention can adopt three schemes to change the diameter of the loofah fiber bundle into 200-1000 μm: (1) pre-treating the natural loofah fiber by using a combined treatment method of alkali and hydrogen peroxide, using a mixture of 5-15% strong sodium oxide solution and 10-15% hydrogen peroxide solution. Soak the loofah in the mixed solution, shake at 37°C for 15-90 minutes, and use deionized water ultrasonic cleaning three times for standby use; (2) using lithium chloride dimethylacetamide solution, lithium chloride dimethylformamide solution, lithium bromide dimethylacetamide solution, lithium bromide dimethylformamide solution. Add 50-100g of anhydrous lithium chloride (60-120g of lithium bromide) dried at 150°C for 6 hours to 1000ml of dimethylacetamide (dimethylformamide), use ultrasonic dispersion for 15-30 minutes to form a transparent solution, soak the loofah in the mixed solution, shake at 37°C for 5-30 minutes to cure, use deionized water ultrasonic cleaning three times, and set aside; (3) Use copper ammonia solution to treat the loofah fiber bundle, add 1L, 0.2mol·L copper sulfate solution to the container, and then add 8mol / L ammonia water, then a light blue basic copper sulfate precipitate is generated, continue to add ammonia water until the precipitate is completely dissolved, then a dark blue solution containing copper ammonia complex ions is obtained, and the end point of the copper ammonia solution preparation is marked by the complete disappearance of the precipitate after adding ammonia water and turning into a transparent blue solution. Soak the loofah in the copper ammonia solution, shake at 37°C for 5-30 minutes to cure, use deionized water ultrasonic cleaning three times, and set aside.

[0031] In the second step of the present invention, calcium sulfate hemihydrate, magnesium oxide, magnesium carbonate, calcium oxide, calcium carbonate, adenosine triphosphate, cyclic adenosine phosphate, calcium dihydrogen phosphate or magnesium pyrophosphate are selected as raw materials as the main components for preparing porous bone repair materials. Calcium sulfate is a required component, magnesium oxide and magnesium carbonate are selected or used in combination, calcium oxide and calcium carbonate are selected or used in combination, calcium dihydrogen phosphate, adenosine triphosphate and cyclic adenosine phosphate are selected or used in combination, and magnesium pyrophosphate is ground (200 mesh and above) as an option. The present invention mixes magnesium oxide / magnesium carbonate / calcium oxide / calcium carbonate with calcium dihydrogen phosphate or adenosine triphosphate and cyclic adenosine phosphate according to a certain proportion, grinds them, adds deionized water to make a paste, dries them in a vacuum at 0-20°C for 8-15 hours, grinds them (200 mesh and above) to form component (A); hydrothermally treats calcium sulfate dihydrate in water vapor at 120°C and 0.4MPa, grinds them (200 mesh and above) to form calcium sulfate hemihydrate (B), mixes A and B according to a certain proportion, adds deionized water, adds magnesium pyrophosphate (C), and mixes them into a slurry (D) for standby use. The composition of the composite D is adjusted according to the proportion of A, B and C, and D is grouted into a loofah to form a required shape and size and solidifies it (the solidification time of the slurry D is controlled within 20-45 minutes according to the proportion and amount of A, B and C) to form a preform.

[0032] The following composition changes occur when magnesium oxide / magnesium carbonate / calcium oxide / calcium carbonate and calcium dihydrogen phosphate or adenosine triphosphate and cyclic adenosine phosphate are present in water. The following is a chemical schematic diagram (not a complete chemical reaction equation) showing the changes:

[0033]

[0034] Among them, MgO can use CaO, CaCO 3 MgCO 3 Instead of calcium dihydrogen phosphate (Ca(H 2 PO 4 ) 2 It can be replaced by adenosine triphosphate (ATP) or cyclic adenosine monophosphate (cAMP), and the products formed in the presence of water are different (but tend to be consistent after high temperature burning at 550℃):

[0035]

[0036] ATP can be replaced by cAMP:

[0037]

[0038] in, It is an intermediate product that can enhance the elasticity and forming properties of the composite during the solidification process.

[0039] In the reaction process of the present invention, the ratio of magnesium oxide or magnesium carbonate to calcium dihydrogen phosphate is (mol): 0.5-1.0:1.0; the ratio of calcium oxide or calcium carbonate to calcium dihydrogen phosphate is (mol): 0.5-1.0:1.0; the ratio of magnesium oxide or magnesium carbonate to adenosine triphosphate (ATP) is (mol) 1.0-2.0:1.0; the ratio of calcium oxide or calcium carbonate to adenosine triphosphate (ATP) is (mol) 1.0-2.0:1.0; the ratio of magnesium oxide or magnesium carbonate to cyclic adenosine monophosphate (cAMP) is (mol) 0.5-1.5:1.0; the ratio of calcium oxide or calcium carbonate to cyclic adenosine monophosphate (cAMP) is (mol) 0.5-1.5:1.0; magnesium oxide, magnesium carbonate, calcium oxide and calcium carbonate can be used alone or in combination, but the ratio (mol) of total magnesium to calcium is (Mg:Ca) 01.-0.5:1.0. Calcium dihydrogen phosphate, adenosine triphosphate and cyclic adenosine phosphate can be used alone or in combination, and the ratio follows the magnesium-calcium ratio (Mg:Ca) 0.1-0.5:1.0.

[0040] The third step of the present invention is to place the pretreated loofah in a metal mold, pour the modulated slurry D into the loofah in the mold, the slurry D completely submerges the loofah, and its height is 1-5mm higher than the loofah, use the mold cover plate to pressurize and compact, its pressure is 2-10MPa, keep it for 20-45 minutes and then open the mold, take out the loofah filled with slurry D, form a solid cuboid after solidification, according to the thickness of the dense layer between the upper layer of the cuboid and the loofah, polish the surface to keep its pure composite D thickness layer at 0.0-1.0mm, 0.0mm is just exposed to the loofah. Through grouting, molding, and shaping, a dense cuboid loofah preformed product E filled with ABC compound is formed.

[0041] The fourth step of the present invention is to sinter the dense rectangular loofah preformed product E filled with ABC compound. Different rectangular loofah preformed products E are sintered and placed in a muffle furnace, the oxygen flow rate of the oxygen inlet of the muffle furnace is 1.0-5.0ml / min, gradually heated to 100-120℃ and retained for 30-45 minutes, then heated to 200℃-250, retained at this temperature for 30-60 minutes, and then heated to 500-550℃, retained at this temperature for 5-10 hours. After that, the oxygen valve is closed, the heating is turned off, the temperature is gradually lowered to room temperature, the muffle furnace is opened, and the preformed product E that has been burned is taken out. A white porous cuboid is obtained, the loofah in the cuboid has been decomposed by high temperature, and the cuboid is removed in the form of carbon dioxide and water, while ATP-Mg, ATP-Ca, cAMP-Mg and cAMP-Ca will decompose, and carbon and nitrogen elements will decompose in the form of gas. At this temperature, the loofah is also decomposed into carbon dioxide and water. The vacancies left after the decomposition of the loofah fibers form fiber channels that are the same as those of the original loofah, forming the final product, a through-hole composite bone repair and reconstruction material F having a loofah-inverse structure.

[0042] The maximum heating temperature of the present invention is 550°C because MgHPO 4 、CaHPO 4 and CaSO 4 After being kept at 550℃ for 5 to 12 hours, the performance can be kept stable, and its composition remains unchanged. It will not be converted into calcium phosphate, magnesium phosphate, etc., nor will it decompose. However, ATP-Mg, ATP-Ca, cAMP-Mg and cAMP-Ca will decompose, and the carbon and nitrogen elements will decompose in the form of gas to form inorganic calcium hydrogen phosphate or magnesium hydrogen phosphate. This invention strictly limits the ratio of calcium oxide / calcium carbonate, magnesium oxide / magnesium carbonate to ATP and cAMP, ensuring that MgHPO is formed after the organic matter is decomposed at 550℃. 4 、CaHPO 4 Rather than other components, such as Mg 3 (PO 4 ) 2 , Ca 3 (PO 4 ) 2 wait.

[0043]

[0044] After long-term pyrolysis at 500-550℃, the organic components in the product are decomposed into ammonia, carbon dioxide and water. At a temperature not higher than 550℃, the product is mainly calcium hydrogen phosphate (CaHPO 4 ), magnesium hydrogen phosphate (MgHPO 4 ) and calcium sulfate (CaSO 4The in-situ channels left after the decomposition of loofah fibers form through-holes, and the ammonia, carbon dioxide and water produced by the decomposition move out of the channels to form escape pores. The final product is a porous structure with through-holes and a composition of

[0045] CaSO 4 -CaHPO 4 -MgHPO 4 A biodegradable porous bone repair and reconstruction material with a main component and an inverse structure to that of loofah.

[0046] Furthermore, the present invention performs shaping of the through-hole composite bone repair and reconstruction material F having the reverse structure of the loofah sponge according to clinical requirements, and grinds the four sides of the cuboid to form the following forms: (1) all four sides are through-hole structures, (2) three sides are through-hole structures, (3) two sides are through-hole structures, and (4) are cut into a cylindrical shape. After the shaping is completed, it is washed with injection water, dried, sterilized by irradiation or epoxy sterilization, and packaged for use.

[0047] The porosity and pore penetration rate of the sterilized composite bone repair and reconstruction material with the reverse structure of loofah were tested, and the degradation, mechanical properties and biological properties were evaluated to obtain the properties of safety, non-toxicity, degradation, high activity, easy growth of blood vessels through the pores to promote bone tissue growth, accelerated material degradation, etc. The present invention adopts the requirements of the T16886 standard, and the sterilized through-porous product F is implanted into the back of New Zealand white rabbits to observe its biosafety such as degradation and inflammation in the body, and implanted into the rabbit femur to observe the bone repair function and efficacy, and the specifications of 10mm*5mm*5mm are selected, and the products with four sides all through the porous structure and two sides through the porous structure are selected for implantation observation. The animal experiment is carried out in accordance with relevant ethical requirements and professional doctors in accordance with clinical surgical procedures.

[0048] Example 1

[0049] (1) Treatment of loofah: Mix 500 ml of 10% sodium hydroxide solution and 500 ml of 10% hydrogen peroxide solution. Cut the dried loofah into a cuboid with a length of 50 mm, a width of 25 mm, and a thickness of 10 mm, soak it in the mixed solution, shake it at 37° C. for 30 minutes, use deionized water ultrasonic cleaning for three times, and dry it for later use.

[0050] (2) Preparation of calcium phosphate magnesium composite salt component A:

[0051] Weigh 40 g of magnesium oxide, 56 g of calcium oxide, and 468 g of calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100 ml of deionized water, stir for 30 minutes, mix well, and dry at 80° C. for 8 hours to form a calcium-magnesium-phosphorus complex (i);

[0052] Weigh 40g magnesium oxide, 28g calcium oxide, and 507g ATP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix well, and dry at 80°C for 8 hours to form ATP-calcium magnesium phosphate complex (ii);

[0053] Weigh 150 g of (i) and 50 g of (ii) and mix to form component A.

[0054] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 100 g of calcium sulfate hemihydrate to form component B.

[0055] Weigh 10 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form group C.

[0056] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0057] (3) Place the loofah treated in process (1) in a metal mold, pour the prepared slurry D into the loofah in the mold, completely submerge the loofah in the slurry D and 2 mm higher than the loofah, use a mold cover to apply pressure and compact, the pressure is 5 MPa, keep it for 15 minutes, then open the mold, take out the loofah filled with slurry D, form a solid rectangular parallelepiped after solidification, grind the surface so that the loofah is just exposed, and form a dense rectangular parallelepiped loofah preformed product E filled with ABC compound.

[0058] (4) Preparation of bone repair products with interpenetrating multi-holes and loofah inverse structure: Place the rectangular loofah preformed product E obtained in process (3) into a muffle furnace, the oxygen flow rate of the muffle furnace oxygen inlet is 2.5 ml / min, gradually heat up to 120°C and keep for 35 minutes, then heat up to 200°C, keep at this temperature for 45 minutes, then heat up to 550°C and keep at this temperature for 8 hours. After that, close the oxygen valve, turn off the heating, gradually cool to room temperature, open the muffle furnace, and take out the completed calcination product. Obtain a white porous rectangular parallelepiped, forming the final product, a interpenetrating composite bone repair and reconstruction material F with a loofah inverse structure.

[0059] (5) The through-hole composite bone repair and reconstruction material F with the reverse structure of loofah obtained in process (4) is subjected to shape modification, and the four sides of the cuboid are polished to form a through-hole porous structure on all four sides. Part of it is cut into 10mm*5mm*5mm specifications as rabbit femoral implant materials, and part of it is cut into 10mm*10mm*8mm as mechanical spline test, porosity test, cytotoxicity test, degradation test, muscle implant test sample trial cutting of the particles or small pieces left. After the shape modification is completed, it is washed with injection water, dried, and the cytotoxicity and implant samples are epoxy sterilized.

[0060] Performance test of the through-hole composite bone repair and reconstruction material with loofah inverse structure obtained by the present invention:

[0061] 1. Porosity and through-hole chlorine test: by density determination drainage method, tested by professional testing agency;

[0062] 2. The aperture is tested by scanning electron microscope;

[0063] 3. Compression test method: Test according to national standards, load speed 1mm / min;

[0064] 4. Degradation test method: Take the injection molded material and perform degradation test in PBS solution: The preparation method of PBS is as follows; accurately weigh KH 2 PO 4 (0.544 g), Na 2 HPO 4 12H 2 O (7.16g), NaCl (16g) and KCl (0.402g) were dissolved in 2L deionized water, and the volume was fixed with a volumetric flask. The pH measurement range was between 7.2-7.4. The sample was placed in a centrifuge tube and a certain amount of PBS solution was added. The volume ratio of PBS solution to sample mass was 1g / 30mL. The centrifuge tube containing the sample was then placed in a constant temperature oscillating box at a temperature of 37°C and a speed of 80rpm / min. The sample was taken out and weighed at 1 (1D), 1w, 4w, 12w and 24w days, and the weight loss rate was calculated. Three control groups were set up for each sample.

[0065] 5. pH determination: The supernatant of the sample was measured with a pH meter and PBS was replaced every 7 days.

[0066] 6. Cytotoxicity and cell proliferation rate test: Prepare the extraction solution in accordance with the provisions of T16886 on biological materials, and calculate the proliferation rate by comparing the standard extract with the blank.

[0067] 7: The functional test of the through-composite bone repair and reconstruction material with the reverse structure of loofah was carried out. According to the requirements of T16886, it was implanted into the back of New Zealand white rabbits to observe its biosafety such as degradation and inflammation in vivo. The specific operation was to implant two 2.5g products into the muscles on both sides of the rabbit spine, three rabbits in each group, and observe the effect. The operation was in accordance with the requirements of T16886.

[0068] 8. Implant the 10mm*5mm*5mm size tissue into the rabbit femur, take samples, embed, slice and observe at 4 and 12 weeks.

[0069] Test results:

[0070] Porosity (%): 63; Pore penetration rate (%): 81.

[0071] Pore ​​size distribution (μm): 350-750.

[0072] Compression strength(MPa):7.5.

[0073] Degradation results: 1w: 20.5%; 4w: 39.4%; 12w: 65.3%; 24w: 92.1%.

[0074] pH value changes: 1w: 7.19: 4w: 7.31; 12w: 7.29; 24w: 7.33.

[0075] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 126% compared with the blank, and the proliferation rate was 139% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0076] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0077] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original tissue bone.

[0078] Example 2 (same as Example 1, the treatment scheme of loofah uses lithium chloride-dimethylacetamide solution)

[0079] (1) Treatment of loofah: Weigh 60g of lithium chloride and dissolve it in 1000ml of dimethylacetamide to form a transparent solution. Cut the dried loofah into a cuboid with a length of 50mm, a width of 25mm and a thickness of 10mm, soak it in the mixed solution, shake it at 37℃ for 10 minutes, clean it with ultrasonic wave for three times with deionized water, and dry it for later use.

[0080] (2)-(5) are the same as in Example 1.

[0081] Test results:

[0082] Porosity (%): 66. Hole penetration rate (%): 85.

[0083] Pore ​​size distribution (μm): 300-800.

[0084] Compression strength(MPa):7.2.

[0085] Degradation results: 1w: 18.6%; 4w: 35.1%; 12w: 61.8%; 24w: 90.9%.

[0086] pH value changes: 1w: 7.21: 4w: 7.32; 12w: 7.31; 24w: 7.34.

[0087] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 128% compared with the blank, and the proliferation rate was 136% after doubling the dilution; compared with the blank, i.e., the culture medium, the extract of the penetrating composite bone repair and reconstruction material with the loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0088] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0089] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0090] Example 3 (same as Example 1, the treatment scheme of loofah uses copper ammonia solution)

[0091] (1) Treatment of loofah: Add 1L of 0.2mol·L copper sulfate solution to a beaker, then add 8mol / L ammonia water, and a light blue basic copper sulfate precipitate will be generated. Continue to add ammonia water until the precipitate is completely dissolved, and then a dark blue solution containing copper ammonia complex ions will be obtained. The end point of the preparation of the copper ammonia solution is marked by the complete disappearance of the precipitate after adding ammonia water and the transformation into a transparent blue solution. Cut the dried loofah into a 50mm long, 25mm wide, and 10mm thick rectangular block, soak it in the mixed solution, shake it at 37℃ for 5 minutes, use deionized water ultrasonic cleaning three times, and dry it for later use.

[0092] (2)-(5) are the same as in Example 1.

[0093] Test results:

[0094] Porosity (%): 70. Hole penetration rate (%): 88.

[0095] Pore ​​size distribution (μm): 280-790.

[0096] Compression strength (MPa): 6.8.

[0097] Degradation results: 1w: 18.2%; 4w: 36.3%; 12w: 60.4%; 24w: 90.2%.

[0098] pH value changes: 1w: 7.21: 4w: 7.28; 12w: 7.33; 24w: 7.33.

[0099] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 126% compared with the blank, and the proliferation rate was 139% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0100] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0101] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone.

[0102] Example 4 (same as Example 1, but with different calcium-phosphorus composite composition, using cAMP instead of ATP)

[0103] (1) Same as Example 1

[0104] (2) Preparation of calcium-phosphorus-magnesium complex salt component A: Weigh 40g magnesium oxide, 56g calcium oxide, and 468g calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form calcium-magnesium-phosphorus complex (i). Weigh 20g magnesium oxide, 14g calcium oxide, and 493g cAMP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form cAMP-calcium-magnesium-phosphorus complex (ii); Weigh 150g of (i) and 50g of (ii) and mix to form component A.

[0105] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 100 g of calcium sulfate hemihydrate to form component B.

[0106] Weigh 10 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form group C.

[0107] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0108] (3)-(5) are the same as in Example 1.

[0109] Test results:

[0110] Porosity (%): 60, pore penetration rate (%): 85.

[0111] Pore ​​size distribution (μm): 310-770.

[0112] Compression strength(MPa):7.2.

[0113] Degradation results: 1w: 15.8%; 4w: 32.%; 12w: 60.1%; 24w: 85.9%.

[0114] pH value changes: 1w: 7.32: 4w: 7.31; 12w: 7.33; 24w: 7.34.

[0115] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 132% compared with the blank, and the proliferation rate was 145% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0116] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0117] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone.

[0118] Example 5 (same as Example 1, but with different calcium-phosphorus composite composition, using cAMP and ATP together)

[0119] (1) Same as Example 1

[0120] (2) Preparation of calcium-phosphorus-magnesium complex salt component A: Weigh 40g magnesium oxide, 56g calcium oxide, 468g calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100ml deionized water, stir for 30 minutes, mix evenly, and dry at 80℃ for 8 hours to form calcium-magnesium-phosphorus complex (i). Weigh 40g magnesium oxide, 28g calcium oxide, 335g ATP, 218g cAMP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix evenly, and dry at 80℃ for 8 hours to form ATP-calcium-magnesium-phosphorus complex (ii); Weigh 150g (i) and 50g (ii) and mix to form component A.

[0121] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 100 g of calcium sulfate hemihydrate to form component B.

[0122] Weigh 10 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form group C.

[0123] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0124] (3)-(5) are the same as in Example 1.

[0125] Test results:

[0126] Porosity (%): 68, pore penetration rate (%): 89.

[0127] Pore ​​size distribution (μm): 300-790.

[0128] Compression strength (MPa): 6.8.

[0129] Degradation results: 1w: 21.3%; 4w: 38.7%; 12w: 66.4%; 24w: 92.5%.

[0130] pH value changes: 1w: 7.31: 4w: 7.32; 12w: 7.33; 24w: 7.33.

[0131] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 143% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0132] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0133] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0134] Example 6 (same as Example 1, the ratio of calcium phosphate is different from that of the example)

[0135] (1) Same as Example 1

[0136] (2) Preparation of calcium-phosphorus-magnesium complex salt component A: Weigh 40g magnesium oxide, 56g calcium oxide, and 468g calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form calcium-magnesium-phosphorus complex (i). Weigh 40g magnesium oxide, 28g calcium oxide, and 507g ATP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form ATP-calcium-magnesium-phosphorus complex (ii); Weigh 180g (i) and 30g (ii) and mix to form component A.

[0137] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 120 g of calcium sulfate hemihydrate to form component B.

[0138] Weigh 10 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form group C.

[0139] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0140] (3)-(5) are the same as in Example 1.

[0141] Test results:

[0142] Porosity (%): 71, pore penetration rate (%): 89.

[0143] Pore ​​size distribution (μm): 300-800.

[0144] Compression strength (MPa): 5.9.

[0145] Degradation results: 1w: 22.7%; 4w: 41.3%; 12w: 67.4%; 24w: 95.5%.

[0146] pH value changes: 1w: 7.05; 4w: 7.211; 12w: 7.30; 24w: 7.32.

[0147] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 132% compared with the blank, and the proliferation rate was 146% after dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with the inverse structure of loofah can provide more nutrition, cell differentiation and proliferation.

[0148] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0149] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0150] Example 7 (same as Example 1, with different amounts of magnesium pyrophosphate component)

[0151] (1) Same as Example 1.

[0152] (2) Preparation of calcium-phosphorus-magnesium complex salt component A: Weigh 40g magnesium oxide, 56g calcium oxide, and 468g calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form calcium-magnesium-phosphorus complex (i). Weigh 40g magnesium oxide, 28g calcium oxide, and 507g ATP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix evenly, and dry at 80°C for 8 hours to form ATP-calcium-magnesium-phosphorus complex (ii); Weigh 150g of (i) and 50g of (ii) and mix to form component A.

[0153] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 100 g of calcium sulfate hemihydrate to form component B.

[0154] Weigh 5 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form group C.

[0155] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0156] (3)-(5) Same as Example 4.

[0157] Test results:

[0158] Porosity (%): 60, pore penetration rate (%): 80.

[0159] Pore ​​size distribution (μm): 300-710.

[0160] Compression strength(MPa):7.5.

[0161] Degradation results: 1w: 21.1%; 4w: 39.7%; 12w: 66.5%; 24w: 93.4%.

[0162] pH value changes: 1w: 7.22: 4w: 7.31; 12w: 7.33; 24w: 7.33.

[0163] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 145% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0164] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0165] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0166] Example 8 (same as Example 5, with different ratios of calcium and phosphate salts)

[0167] (1) Same as Example 1.

[0168] (2) Preparation of calcium-phosphorus-magnesium complex salt component A: Weigh 40g magnesium oxide, 56g calcium oxide, 468g calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100ml deionized water, stir for 30 minutes, mix evenly, and dry at 80℃ for 8 hours to form calcium-magnesium-phosphorus complex (i). Weigh 40g magnesium oxide, 28g calcium oxide, 335g ATP, 218g cAMP, mix and grind to 200 mesh, add 150ml deionized water, stir for 30 minutes, mix evenly, and dry at 80℃ for 8 hours to form ATP-calcium-magnesium-phosphorus complex (ii); Weigh 150g (i) and 50g (ii) and mix to form component A.

[0169] Weigh 500 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 120° C. and 0.4 MPa for 9 hours to form calcium sulfate hemihydrate, grind it into fine powder (200 mesh and above), and weigh 120 g of calcium sulfate hemihydrate to form component B.

[0170] Weigh 10 g of magnesium pyrophosphate and grind it into fine powder (200 mesh and above) to form component C.

[0171] Component A, component B and component C are mixed, and 200 ml of deionized water is added to form a slurry to form slurry D for later use. In order to prevent slurry D from solidifying, it is poured into the loofah as soon as possible.

[0172] (3)-(5) are the same as Example 4.

[0173] Test results:

[0174] Porosity (%): 72; Pore penetration rate (%): 90.

[0175] Pore ​​size distribution (μm): 300-800.

[0176] Compression strength(MPa):6.5.

[0177] Degradation results: 1w: 21.7%; 4w: 39.9%; 12w: 66.8%; 24w: 93.3%.

[0178] pH value changes: 1w: 7.15; 4w: 7.26; 12w: 7.30; 24w: 7.33.

[0179] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 136% compared with the blank, and the proliferation rate was 150% after dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with the inverse structure of loofah can provide more nutrition, cell differentiation and proliferation.

[0180] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0181] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0182] Example 9 (same as Example 1, but with different pressures for preparing rectangular loofahs by grouting and molding)

[0183] (1)-(2) Same as Example 1.

[0184] (3) The loofah treated in process (1) is placed in a metal mold, and the prepared slurry D is poured into the loofah in the mold, so that the slurry D completely submerges the loofah and its height is 4 mm higher than the loofah. The mold cover is used to pressurize and compact, and the pressure is 10 MPa. After maintaining for 15 minutes, the mold is opened, and the loofah filled with slurry D is taken out to form a solid rectangular parallelepiped after solidification. The surface is polished so that the loofah is just exposed, forming a dense rectangular parallelepiped loofah preformed product E filled with ABC composite.

[0185] (4)-(5) Same as Example 1.

[0186] Test results:

[0187] Porosity (%): 60. Hole penetration rate (%): 80.

[0188] Pore ​​size distribution (μm): 300-700.

[0189] Compression strength(MPa):9.1.

[0190] Degradation results: 1w: 18.3%; 4w: 36.1%; 12w: 62.2%; 24w: 89.4%.

[0191] pH value changes: 1w: 7.20; 4w: 7.29; 12w: 7.33; 24w: 7.34.

[0192] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 144% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0193] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0194] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone.

[0195] Example 10 (same as Example 1, but with different muffle furnace pyrolysis temperature)

[0196] (1)-(3) Same as Example 1

[0197] (4) Prepare a bone repair product with a porous structure and a reverse structure of a loofah. The rectangular loofah preformed product E obtained in process (3) is placed in a muffle furnace with an oxygen flow rate of 2.5 ml / min at the oxygen inlet of the muffle furnace. The temperature is gradually raised to 120°C and retained for 35 minutes, then raised to 200°C and retained at this temperature for 45 minutes, then raised to 525°C and retained at this temperature for 10 hours. After that, the oxygen valve is closed, the heating is turned off, the temperature is gradually lowered to room temperature, the muffle furnace is opened, and the burnt product is taken out. A white porous rectangular block is obtained to form the final product, a composite bone repair and reconstruction material F with a reverse structure of a loofah.

[0198] (5) Same as Example 1.

[0199] Test results:

[0200] Porosity (%): 60. Hole penetration rate (%): 85.

[0201] Pore ​​size distribution (μm): 310-900

[0202] Compression strength(MPa):6.5.

[0203] Degradation results: 1w: 19.4%; 4w: 38.8%; 12w: 64.9%; 24w: 91.8%.

[0204] pH value changes: 1w: 7.20: 4w: 7.30; 12w: 7.32; 24w: 7.33.

[0205] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 137% compared with the blank, and the proliferation rate was 149% after doubling the dilution; compared with the blank, i.e., culture medium, the extract of the penetrating composite bone repair and reconstruction material with a loofah inverse structure could provide more nutrition, cell differentiation and proliferation.

[0206] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on 1 day, 1 week or 4 weeks. The wound was basically healed in 1 week and completely healed in 4 weeks.

[0207] Femoral repair effect: After 4 weeks, a large number of blood vessels and blood vessels passed through the through-holes, after 12 weeks, the through-holes were covered with new bone and most of the material was degraded, and after 24 weeks, the new bone was basically connected as a whole with no interface with the original bone tissue.

[0208] Comparative Example 1, calcium hydrogen phosphate / calcium sulfate complex

[0209] Weigh 60g of calcium sulfate hemihydrate and 40g of calcium hydrogen phosphate, mix well, add 50ml of water for injection and stir into a paste, blend evenly, put the blended product into a mold to make a test sample, take it out after curing and put it into a muffle furnace. The oxygen flow rate of the oxygen inlet of the muffle furnace is 2.5ml / min, gradually heat up to 120℃ and keep it for 35 minutes, then heat up to 200℃, keep it at this temperature for 45 minutes, then heat up to 550℃ and keep it at this temperature for 10 hours. After that, close the oxygen valve, turn off the heating, gradually cool down to room temperature, open the muffle furnace, and take out the completed burning product.

[0210] Test results:

[0211] Porosity (%): 20. Hole penetration rate (%): 15.

[0212] Pore ​​size distribution (μm): 100-300.

[0213] Compression strength(MPa):15.

[0214] Degradation results: 1w: 15.4%; 4w: 28.8%; 12w: 45.3%; 24w: 59.8%.

[0215] pH value changes: 1w: 7.13; 4w: 7.21; 12w: 7.29; 24w: 7.30.

[0216] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 115% compared with the blank, and the proliferation rate after double dilution was 126%, which was slower than that of the example.

[0217] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on the 1st day, 1st week and 4th week. The wound was mostly healed in 1 week and basically healed in 4 weeks.

[0218] Femoral repair effect: It was difficult for blood vessels to pass through the surrounding areas. After 12 weeks, the material was surrounded by new bones and the material was partially degraded. After 24 weeks, one-third of the material was still wrapped by new bones. The effect was poorer than that of the embodiment.

[0219] Comparative Example 2: Calcium sulfate calcium hydrogen phosphate hydrogen peroxide foaming compound

[0220] Weigh 60g of calcium sulfate hemihydrate and 40g of calcium hydrogen phosphate, mix well, add 45ml of water for injection, and add 5ml of 10% hydrogen peroxide to mix well. Put the mixed product into the mold to make a test sample, take it out after curing, and put it into the muffle furnace. The oxygen flow rate of the oxygen inlet of the muffle furnace is 2.5ml / min. Gradually heat it to 120℃ and keep it for 35 minutes, then heat it to 200℃, keep it at this temperature for 45 minutes, then heat it to 550℃ and keep it at this temperature for 10 hours. After that, close the oxygen valve, turn off the heating, gradually cool it to room temperature, open the muffle furnace, and take out the burned product.

[0221] Test results:

[0222] Porosity (%): 75. Hole penetration rate (%): 50; the through-porosity is lower than that of the embodiment.

[0223] Pore ​​size distribution (μm): 100-1500, which is wider than that of the embodiment.

[0224] Compression strength (MPa): 3.5. The strength is relatively low compared to the examples.

[0225] Degradation results: 1w: 19.4%; 4w: 32.7%; 12w: 65.3%; 24w: 85.8%.

[0226] pH value changes: 1w: 7.16; 4w: 7.20; 12w: 7.25; 24w: 7.30.

[0227] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 118% compared with the blank, and the proliferation rate after double dilution was 130%, which was slower than that of the example.

[0228] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on the 1st day, 1st week and 4th week. The wound was mostly healed in 1 week and basically healed in 4 weeks.

[0229] Femoral repair effect: At four weeks, some blood vessels passed through the pores to form new bone, at 12 weeks, more new bone was formed through the pores, the material was partially degraded, at 24 weeks, some new bone was connected, and the effect was poorer than that of the embodiment.

[0230] Comparative Example 3: Same as Example 1, except that ATP calcium phosphate is removed.

[0231] Test results:

[0232] Porosity (%): 55. Hole penetration rate (%): 70; the through-porosity is lower than that of the embodiment.

[0233] Pore ​​size distribution (μm): 300-1000, which is wider than that of the embodiment.

[0234] Compression strength (MPa): 4.1. The strength is relatively low compared to the examples.

[0235] Degradation results: 1w: 20.1%; 4w: 33.6%; 12w: 66.1%; 24w: 89.4%.

[0236] pH value changes: 1w: 7.21: 4w: 7.30; 12w: 7.33; 24w: 7.33.

[0237] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 119% compared with the blank, and the proliferation rate after double dilution was 134%, which was slightly slower than that of the example.

[0238] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on the 1st day, 1st week and 4th week. The wound was mostly healed in 1 week and basically healed in 4 weeks.

[0239] Femoral repair effect: At four weeks, some blood vessels passed through the pores to form new bone, at 12 weeks, more new bone was formed through the pores, and the material was partially degraded, at 24 weeks, most of the new bone links were connected, and the effect was poorer than that of the embodiment.

[0240] Comparative Example 4 is the same as Example 1, but the sintering temperature is 650°C, which is 100°C higher than that of Example 1.

[0241] Test results:

[0242] Porosity (%): 66. Hole penetration rate (%): 80.

[0243] Pore ​​size distribution (μm): 300-1500, which is wider than that of the embodiment.

[0244] Compression strength (MPa): 2.7. The strength is relatively low compared to the examples.

[0245] Degradation results: 1w: 12.9%; 4w: 25.8%; 12w: 57.7%; 24w: 65.3%. The pyrolysis temperature is too high, and the calcium hydrogen phosphate is converted into calcium phosphate, which is difficult to degrade.

[0246] pH value changes: 1w: 7.23: 4w: 7.31; 12w: 7.33; 24w: 7.34.

[0247] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 120% compared with the blank, and the proliferation rate was 135% after doubling the dilution.

[0248] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on the 1st day, 1st week and 4th week. The wound was mostly healed in 1 week and basically healed in 4 weeks.

[0249] Femoral repair effect: At four weeks, some blood vessels passed through the pores to form new bone, at 12 weeks, more new bone was formed through the pores, the material was partially degraded, at 24 weeks, some new bone was connected, and the effect was poorer than that of the embodiment.

[0250] Comparative Example 5: Same as Example 1, all components are the same as Example 1. No loofah is used as a template and no high temperature pyrolysis is performed.

[0251] The product D formed by curing ABC of Example 1 was tested.

[0252] Test results:

[0253] Porosity (%): 28. Hole penetration rate (%): 11; Porosity and through-hole rate are both lower than those of the embodiment.

[0254] Pore ​​size distribution (μm): 100-300. The pore size is very small, which is not conducive to cell growth.

[0255] Compression strength (MPa): 15.6.

[0256] Degradation results: 1w: 20.1%; 4w: 31.4%; 12w: 51.6%; 24w: 64.6%. The surface is covered with deposited calcium and phosphate salts, and the degradation is slow in the later stage.

[0257] pH value changes: 1w: 7.19; 4w: 7.27; 12w: 7.31; 24w: 7.33.

[0258] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 125% compared with the blank, and the proliferation rate was 140% after double dilution.

[0259] After muscle wound surgery: no redness, swelling, exudation or fluid accumulation occurred on the 1st day, 1st week and 4th week. The wound was mostly healed in 1 week and basically healed in 4 weeks.

[0260] Femoral repair effect: blood vessels cannot pass through the surrounding area, new bone is formed around the material, 12 more new bone is formed around the material, the material is partially degraded, but cannot pass through the inside of the material, 24 part of the new bone around the material is connected, and part of the material is wrapped in the middle of the new bone. The repair effect is worse than that of the embodiment.

[0261] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a through-hole bone repair material, characterized in that: The preparation method comprises the following steps: 1) Preparing bone repair raw material slurry: mixing the raw materials of the bone repair material with water to form a bone repair raw material slurry; 2) preparing a bone repair preform: placing the bone repair raw material slurry in a loofah to fully immerse the loofah so that the bone repair slurry fills the loofah, and then solidifying the slurry to obtain a bone repair preform; 3) Sintering treatment: The bone repair preform is sintered to remove the loofah, so as to obtain the bone repair material with a through-hole structure.

2. The method for preparing a through-hole bone repair material according to claim 1, characterized in that: In step 1), the raw materials of the bone repair material include components in the following proportions: 35-55 parts by weight of calcium-phosphate-magnesium complex salt, 25-55 parts by weight of calcium sulfate hemihydrate, and 0-5 parts by weight of magnesium pyrophosphate; wherein the molar ratio of magnesium to calcium in the calcium-phosphate-magnesium complex salt is 0.1-0.5:

1.

3. The method for preparing a through-hole bone repair material according to claim 1 or 2, characterized in that: In step 1), the ratio of the raw material of the bone repair material to water is 1:0.5-1.5 (g / mL).

4. The method for preparing a through-hole bone repair material according to any one of claims 1 to 3, characterized in that: In step 1), the calcium-phosphorus-magnesium composite salt is prepared by the following method: magnesium salt, calcium salt and phosphorus-containing substance are mixed and ground, then water is added to make a paste, and then vacuum dried to obtain the calcium-phosphorus-magnesium composite salt; wherein the phosphorus-containing substance is at least one of calcium dihydrogen phosphate, adenosine triphosphate or cyclic adenosine monophosphate; Furthermore, the magnesium salt is at least one of MgO or MgCO3, and the calcium salt is at least one of CaO or CaCO3.

5. The method for preparing a through-hole bone repair material according to claim 4, characterized in that: In step 1), the bone repair raw material slurry is prepared by the following method: (1) Weigh 40-50 g of magnesium oxide, 50-60 g of calcium oxide, and 450-470 g of calcium dihydrogen phosphate, mix and grind to 200 mesh, add 100-150 ml of deionized water, stir for 25-35 minutes, mix well, and dry at 70-80° C. for 5-10 hours to form a calcium-magnesium-phosphorus complex 1; Weigh 20-40 g of magnesium oxide, 14-28 g of calcium oxide, and 493-553 g of a phosphorus-containing substance, mix and grind to 200 mesh, add 140-160 ml of deionized water, stir for 25-35 minutes, mix evenly, and dry at 70-80° C. for 5-10 hours to form a calcium-magnesium-phosphorus complex 2; Weigh 1 / 150-180 g of the composite and 2 / 30-50 g of the composite and mix them to form component A; 2) Weigh 450-550 g of calcium sulfate dihydrate and perform hydrothermal treatment in water vapor at 110-130° C. and 0.1-0.5 MPa for 5-10 hours to form calcium sulfate hemihydrate, which is then ground to 200 mesh or more as component B; 3) weighing magnesium pyrophosphate and grinding it to 200 mesh or above to form component C; 4) Mix 200-210 g of component A, 100-120 g of component B and 5-10 g of component C, add 150-250 ml of deionized water to mix into a slurry to form a bone repair raw material slurry.

6. The method for preparing a through-hole bone repair material according to any one of claims 1 to 5, characterized in that: In step 2), the loofah is pretreated before use so that the fiber diameter of the loofah is 200-1000 μm.

7. The method for preparing a through-hole bone repair material according to claim 6, characterized in that: The pretreatment method comprises the following steps: firstly dividing the selected loofah according to its veins and cutting it into regular cubes with a length of 10 mm to 200 mm, a width of 10 mm to 50 mm and a height of 0.5 mm to 20 mm; then soaking the loofah in a treatment solvent and then air-drying it for later use; the treatment solvent is selected from the group consisting of sodium hydroxide-hydrogen peroxide solution, lithium chloride-dimethylacetamide solution, lithium bromide-dimethylacetamide solution, lithium chloride-dimethylformamide solution, lithium bromide-dimethylformamide solution or cuprammonia solution.

8. The method for preparing a through-hole bone repair material according to any one of claims 1 to 7, characterized in that: In step 3), the sintering process is as follows: placing the bone repair preform into a muffle furnace, gradually heating it to 100-120°C and keeping it for 30-45 minutes, then heating it to 200-250°C and keeping it for 30-60 minutes, then heating it to 500-550°C and keeping it for 5-12 hours.

9. The method for preparing a through-hole bone repair material according to any one of claims 1 to 8, characterized in that: The preparation method of the through-hole bone repair material also includes step 4): post-processing the through-hole bone repair material according to clinical requirements: cutting and grinding the through-hole bone repair material into shape and size, washing with injection water, drying, using radiation sterilization or epoxy sterilization, and finally packaging for use.

10. A through-hole bone repair material, characterized in that: The bone repair material is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Magnesium oxide for magnesium phosphate concrete, preparation method of magnesium oxide and magnesium phosphate concrete

    CN102515576A

  • Preparation method of degradable porous structural tissue engineering bracket with high strength

    CN103463685A

  • Degradable porous composite stent material for bone transplantation

    CN105597158A

  • Degradable magnesium / zinc-containing calcium phosphate-calcium sulfate porous composite biological scaffold

    CN106310363A

  • Porous composite ceramic capable of guiding bone regeneration and preparation method of porous composite ceramic

    CN110251723A

Cited By

  • Multi-dimensional bionic scaffold with space-time synergistic osteogenesis function and preparation method

    CN120754327A